2023
DOI: 10.1017/ash.2022.331
|View full text |Cite
|
Sign up to set email alerts
|

Impact of phenotypic rapid diagnostic assay on duration of empiric antibiotics for gram-negative bacteremia

Abstract: Objective: Rapid diagnostic tests (RDTs) are increasingly being implemented as antimicrobial stewardship tools to facilitate antibiotic modification and reduce complications related to their overutilization. We measured the clinical impact of a phenotypic RDT with antimicrobial stewardship (AMS) in the setting of gram-negative bacteremia. Setting and participants: In this single-center retrospective cohort study, we evaluated adult patients with gram-negative bacteremia who received at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In this study, we also evaluated the possible effect of using RDT on mortality in patients with MDR GNB bacteremia. Mohayya et al recently showed that reduction in the duration of inadequate empirical treatment was associated with better outcomes and although not statistically significant, the finding was notable and may favor the use of RDT as a useful tool for adequate targeted treatment in the context of antimicrobial resistance strategies [ 55 ]. Although the implementation of antibiotic stewardship protocols and the progress and handy release of diagnostic tools might optimize appropriate empirical therapy, selecting appropriate empirical therapy remains a challenge, particularly for resistant pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we also evaluated the possible effect of using RDT on mortality in patients with MDR GNB bacteremia. Mohayya et al recently showed that reduction in the duration of inadequate empirical treatment was associated with better outcomes and although not statistically significant, the finding was notable and may favor the use of RDT as a useful tool for adequate targeted treatment in the context of antimicrobial resistance strategies [ 55 ]. Although the implementation of antibiotic stewardship protocols and the progress and handy release of diagnostic tools might optimize appropriate empirical therapy, selecting appropriate empirical therapy remains a challenge, particularly for resistant pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…A recent consensus document produced by several scientific societies, brings together several recommendations, including the concept of the importance of rapid diagnostics in the identification and determination of antibiotic susceptibility [46]. These methods also reduce the duration of empirical antimicrobial therapy [46,47]. The integration of a molecular and a phenotypic approach is relevant, considering that there has been a change in the Cortegiani et al J Anesth Analg Crit Care (2023) 3:11 current epidemiology regarding carbapenemase-resistant Enterobacterales.…”
Section: Statements and Rationalesmentioning
confidence: 99%